2019
DOI: 10.3390/ma12233834
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Print Orientation on Surface Roughness in Fused Deposition Modeling (FDM) Processes

Abstract: In the present paper, we address the influence of print orientation angle on surface roughness obtained in lateral walls in fused deposition modelling (FDM) processes. A geometrical model is defined that considers the shape of the filaments after deposition, in order to define a theoretical roughness profile, for a certain print orientation angle. Different angles were considered between 5° and 85°. Simulated arithmetical mean height of the roughness profile, Ra values, were calculated from the simulated profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 32 publications
6
70
0
Order By: Relevance
“…The great influence of layer height on surface roughness of FDM printed parts has been reported by different authors [ 22 , 26 , 27 ]. In the present work, the lowest Ra value achieved in the lateral walls of the parts that were considered in the present research was around 3.9 µm when low layer height, low temperature and a high speed are selected.…”
Section: Resultsmentioning
confidence: 94%
“…The great influence of layer height on surface roughness of FDM printed parts has been reported by different authors [ 22 , 26 , 27 ]. In the present work, the lowest Ra value achieved in the lateral walls of the parts that were considered in the present research was around 3.9 µm when low layer height, low temperature and a high speed are selected.…”
Section: Resultsmentioning
confidence: 94%
“…In addition, roughness is greatly influenced by the measurement direction. The higher the inclination of a wall is, the higher the theoretical value of the Ra parameter becomes [ 12 , 13 ]. Regarding other roughness parameters, in a previous study with PLA cylindrical parts, it was found that, as a general trend, slightly negative Rsk (skewness) values are obtained in lateral walls of printed parts, corresponding to slightly sharp valleys and rounded peaks.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to method-specific artefacts, e.g. tip convolution in the contact methods 26 that affect directly the statistical results across different scales 27 , 28 , effects related to finite area are universal. They would impact even ideal measurements in which the measured profile perfectly traces the surface topography.…”
Section: Introductionmentioning
confidence: 99%